2007
DOI: 10.1302/0301-620x.89b8.18809
|View full text |Cite
|
Sign up to set email alerts
|

Retrieval analyses of highly cross-linked polyethylene acetabular liners four and five years after implantation

Abstract: Two Durasul highly crosslinked polyethylene liners were exchanged during revision surgery four and five years after implantation, respectively. The retrieved liners were evaluated macroscopically and surface analysis was performed using optical and electron microscopy. A sample of each liner was used to determine the oxidation of the material by Fourier transform infrared spectroscopy. Samples of the capsule were examined histologically. The annual wear rate was found to be 0.010 and 0.015 mm/year, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 19 publications
(14 reference statements)
2
13
1
Order By: Relevance
“…In agreement with prior immunohistochemical [3,5,12,28,36,40,41] or histologic [42,59] studies, the predominant cells in both cohorts were macrophages and T cells. The contribution of neutrophils was negligible, and even the largest neutrophil infiltration (8.6/mm 2 ; Table 2) represented only a fraction of what would be considered evidence of subclinical infection [4,7,17,56].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In agreement with prior immunohistochemical [3,5,12,28,36,40,41] or histologic [42,59] studies, the predominant cells in both cohorts were macrophages and T cells. The contribution of neutrophils was negligible, and even the largest neutrophil infiltration (8.6/mm 2 ; Table 2) represented only a fraction of what would be considered evidence of subclinical infection [4,7,17,56].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to a previous study of two patient tissues from revised HXLPE liners, we found macrophages, a few lymphocytes, and limited amounts of UHMWPE wear debris [42]. However, immunohistochemistry was not done in that study [42] to quantify individual cell types or evaluate colocalization of the inflammatory response with wear debris.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The advantage of XLPE is an apparent reduction of wear rate versus conventional polyethylene (Beksac et al, 2009 (Beksac et al, 2009;McCalden et al, 2009;Bitsch et al, 2008;Engh et al, 2006;Dorr et al, 2005). To our knowledge, only a single retrieval analysis of one type of XLPE liner implanted for greater than four years exists in literature (Knahr et al, 2007). That study reports on two XLPE liners implanted during primary 1751-6161/$ -see front matter c 2010 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%